Continuous biocatalytic recovery of neodymium and europium. Issue 11 (7th February 2015) - Murray, Angela J.; Singh, Sarah; Vavlekas, Dimitrios; Tolley, Mark R.; Macaskie, Lynne E.
<x xml:space="preserve">Abstract</x> Bacterial biofilms recover key rare earth elements as nanocrystalline metal phosphates via robust phosphatase activity, more efficiently than polyacrylamide gel-immobilized cells and show promise for bioremediation and biocatalyst manufacturing.